2014
DOI: 10.1002/acn3.128
|View full text |Cite|
|
Sign up to set email alerts
|

Dopaminergic therapy affects learning and impulsivity in Parkinson's disease

Abstract: ObjectiveThe aim was to examine the effect of dopaminergic medication on stimulus-response learning versus performing decisions based on learning.MethodTo see the effect of dopaminergic therapy on stimulus-response learning and response selection, participants with Parkinson’s disease (PD) were either tested on and/or off their prescribed dose of dopaminergic therapy during different testing days. Forty participants with PD and 34 healthy controls completed the experiment on consecutive days. On Day 1, partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 45 publications
2
13
0
Order By: Relevance
“…In paradigms other than the Go No-go task, there is evidence that motor impulsivity is improved by dopaminergic therapy. In a study by Hiebert et al ( 2014a ), PD patients off dopaminergic medications demonstrated greater motor impulsivity in the form of enhanced facilitation in the congruent condition of a modified Stroop task that was in fact normalized relative to performance of age-matched controls by dopaminergic treatment. This study provided an example of impulsive behavior, specifically motor impulsivity, being improved , not worsened, by dopaminergic therapy, supporting the notion that impulsivity is not a unitary construct (Antonelli et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In paradigms other than the Go No-go task, there is evidence that motor impulsivity is improved by dopaminergic therapy. In a study by Hiebert et al ( 2014a ), PD patients off dopaminergic medications demonstrated greater motor impulsivity in the form of enhanced facilitation in the congruent condition of a modified Stroop task that was in fact normalized relative to performance of age-matched controls by dopaminergic treatment. This study provided an example of impulsive behavior, specifically motor impulsivity, being improved , not worsened, by dopaminergic therapy, supporting the notion that impulsivity is not a unitary construct (Antonelli et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…PD patients with greater motor impulsivity are more susceptible to falls (Ahlskog, 2010 ; Wylie et al, 2012 ). In contrast to its effect of motivational/cognitive impulsivity, there is evidence that dopaminergic therapy might improve motor impulsivity in PD (Fera et al, 2007 ; Hiebert et al, 2014a ; Caillava-Santos et al, 2015 ; van Wouwe et al, 2016 ). Our aim in the current study, was therefore to investigate the effect of DA on motor rather than cognitive impulsivity using the Go No-go paradigm (Simmonds et al, 2008 ; Wright et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Implicit in the reward prediction error model of dopamine function is the idea that decreased release of dopamine will track with a decreasing capability to perform stimulus‐response and reinforcement learning. In humans with PD, sometimes l ‐dopa does not improve reinforcement learning deficits (Shiner et al ) and might worsen them (Hiebert et al ; Macdonald et al ) though other experiments have shown improved reinforcement learning while on PD medication, increasing learning rates from positive, rewarded outcomes without impacting potential negative prediction errors on negative outcomes (Frank et al , ). While this outcome may call into question how reliable the RPE hypothesis of mdDA function is regarding humans, it is still difficult to account for all variables in clinical scenarios.…”
Section: Neurodevelopment Of Mesodiencephalic Dopamine Neuronsmentioning
confidence: 99%
“…The DS is ascribed a role in both early, goal‐directed learning [Brovelli et al, ; O'Doherty et al, ] and late‐stage learning of stimulus–response associations to the point of automaticity [Ashby et al, ; Balleine et al, ]. Challenging this notion, however, learning is often preserved in patients [Exner et al, ; Hiebert et al, ; MacDonald et al, ; Vo et al, ] and in animals [Atallah et al, ] with DS dysfunction. Features of standard stimulus–response learning methodology potentially shed light on this controversy as detailed in the paragraphs below.…”
Section: Introductionmentioning
confidence: 99%